Efforts to Improve Fine Motor Skills through Weaving Activities at RA Insan Mulia - Astutik, Wike Norvila; Palupi, Wike Dwi; Astutik, Wiji; Wijiati; Hariyanti, Wiji (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to examine the effect of weaving activities on improving fine motor skills in children at RA Insan Mulia. This study used a classroom action research approach with two cycles, where each cycle consisted of four weeks. The subjects of this study were kindergarten students at RA Insan Mulia. Data were collected through direct observation, initial and final tests of fine motor skills, and feedback from parents. The results of the study showed that weaving activities had a positive impact on the development of students' fine motor skills. Before this activity began, many students had difficulty in performing tasks that required hand-eye coordination, such as drawing and cutting. However, after participating in weaving activities regularly, students showed significant improvements in their motor skills, especially in terms of hand-eye coordination, grip strength, and finger skills. In addition, weaving activities also improved students' concentration, social skills, and self-confidence. Weaving activities involving various materials, such as paper, yarn, and cloth, have been shown to be effective in improving fine motor skills because they provide students with the opportunity to practice controlling objects with various textures and thicknesses. The repetitive weaving process also helps students strengthen their hand muscles and improve their accuracy and attention to detail. Although most students showed significant progress, some students still needed additional support to master the weaving technique well. Therefore, this study emphasizes the importance of an individualized learning approach that is responsive to the needs of each student. Overall, the results of this study indicate that weaving activities are an effective method for improving fine motor skills in early childhood, and can support their cognitive, social, and emotional development. This activity can be used as an alternative in the early childhood education curriculum to optimize motor development and other aspects.